Digital Pedagogical Innovations in English Language Education: A Systematic Literature Review - Khatimah, Husnul (BATARA DIDI : English Language Journal, 2023)
The objectives of this systematic review are as follow: to identify and evaluate integration of digital technologies into the teaching and learning of English language and to compare it with traditional non-digital methods. The study conducted in this paper used systematic literature review. This study used structured approach. Research on the impact of digital technology tools on enhancing language learning, with the use of AI-assisted learning applications, learning through mobile devices, game-based learning application. Based on the current literature review, educational technology offers significant advantage including, individualized learning instructions, content, real interaction, and the ability of gaining pragmatic experience in realistic virtual contexts. However, some of the current concerns which are still a thorny issue are the lack of access to digital technologies in homes and schools, the need for faculty development and the costs of leveraging technologies. The outcome of this study shows that digital innovations play a significant role in improving language learning and therefore lessons learnt should be applied affirmatively using the technologies alongside other conventional methods. Being a blend of the formal and the informal modes of learning methodologies this hybrid approach could lead to better language learning outcomes as compared to formal or technology-based approaches.